Analisis Aliran Air Bawah Permukaan Dengan Menggunakan Metode Geolistrik - Muhammad Ragil Setiawan; Bilal Al Farishi; Lea Kristi Agustin (Jurnal Pendidikan Teknologi Kejuruan, 2019)
Cean water is needed in a human community. The need for clean water can be taken from subsurface water through a pumping process. Efforts to get clean water that has sustainability can be done by knowing the direction of the aquifer flow. The direction of the aquifer flow can be known through subsurface modeling. This study uses the geoelectric method in modeling the subsurface layer to determine the position of the aquifer. Based on the subsurface model, the average depth of an aquifer is between 30-100 meters. The subsurface model shows the type of aquifer depressed with a clay layer as the upper and lower limits of the aquifer. The subsurface water is estimated to have a flow direction from East to West in a confined aquifer.